"You know your own fistula, it becomes a part of you"—Patient perspectives on vascular access: A semistructured interview study. Issue 1 (22nd July 2015) - Taylor, Matthew J.; Hanson, Camilla S.; Casey, Jordan R.; Craig, Jonathan C.; Harris, David; Tong, Allison
Abstract: The success of hemodialysis depends on functional vascular access but such an invasive, semipermanent intervention can be confronting for patients. Vascular access complications are potentially life threatening and reduce treatment satisfaction and quality of life. This study aims to describe patient perspectives on vascular access. Face‐to‐face, semistructured interviews were conducted with 26 adult patients receiving hemodialysis with any form of vascular access at two dialysis units in Australia. The transcripts were analyzed using thematic analysis. We identified five major themes describing patient perspectives on vascular access: developing mental fortitude for access (accepting necessity for survival, self‐advocacy, experiential confidence and competency, dependency on others, gaining vascular knowledge), device intrusiveness on the body (restricting normal function, finding compensatory solutions, bodily invasion, confronting appearance), inhibiting pain (aversion to surgery, persisting needle anxieties), exposure to dire health consequences (resigning to inevitable failure, anticipating serious complications, technological skepticism, wary of medical incompetence), and imposing burdens (generating additional expenses, encumbering family members). Patients with a vascular access rely on a precarious lifeline, which is confronting, intrusive, and burdensome. Some develop mental resilience to cope with the pain and invasiveness of vascular access. The results suggest that more attention to address needle anxieties, self‐advocacy, lifestyle disruption, fear of complications, and concern for caregiver burden may improve treatment satisfaction and outcomes for patients on hemodialysis.